A Novel Method to Locate Intracranial Anatomic Landmarks of Sella Using Three-Dimensional Computed Tomography Reconstruction Images for Endoscopic Endonasal Transsphenoidal Surgery. Issue 7 (October 2015) - Wu, Pinghua; Zeng, Huiken; Tan, Xiangliang; Ouyang, Jun; Zhong, Shizen
Abstract : Objective: To help surgeons to locate the intracranial anatomic landmarks when performing endoscopic endonasal tanssphenoidal surgery using measurements based on three-dimensional computed tomography (CT) reconstruction images. Method: High-resolution axial CT images at the thickness of 0.6 mm, and reconstructed 0.41-mm-thick gapless sagittal and coronal CT images were taken from 111 subjects. Using mimics software, first located the points of nasal spine, midpoint of the posterior hard palate and the basic line between them. Then located the medial edge of foramen lacerums, optic canals, midpoints of tuberculum sellae and posterior-inferior sellar floor, measured their distances to nasal spine and angles between the line connecting these structures to nasal spine and the basic line. Results: The mean distance from nasal spine to optic canal is 73.12 ± 4.10 mm, and the corresponding angle is 39.79° ± 3.13°. The distance from the medial edge of foramen lacerum to nasal spine is 79.91 ± 4.01 mm, and the corresponding angle is 23.27° ± 2.89°. The distances from midpoints of the tuberculum sellae and posterior-inferior sellar floor to nasal spine are 76.16 ± 4.56 mm and 82.05 ± 4.81 mm, and the corresponding angles are 34.97° ± 3.24° and 26.39° ± 3.51°, respectively. The distances between both foramen lacerums and optic canals are 22.54 ± 3.25 and 23.44 ± 3.49 mm, respectively. The distance from the midpoint of tuberculum sellae to posterior-inferior sellar floor is 13.33 ± 1.87 mm. Conclusion: The current study provides information about intracranial anatomic landmarks, which can help neurosurgeons to locate them and avoid relative complications during endoscopic endonasal transsphenoid surgery. The measurements can be used as surgical indicators to investigate these anatomic landmarks.